O nonsense revisitado: a estética de ruptura de Edward Lear em diálogo com o contemporâneo de Renato Pompeu em Quatro-olhos - Granato, Fernanda Marques (2015)
This dissertation has as its aim to retrieve the concept of the nonsense genre with the purpose of testing the hypothesis of a possible dialogue between texts from two literary works of different characteristics and of different times: Viagem numa peneira, by Edward Lear (1846), and Quatro-olhos, by Renato Pompeu (1976). The studies carried out were able to ascertain that, among the analyzed texts, there are traces that make possible not only to bring the two closer together, but also to do a reinterpretation of the nonsense genre in the context of the literary contemporaneity. In order to develop this proposal, we have elected a few authors that give support to the analysis of the fictional works, such as: Aristotle (2011) and Croce (1995), on genre; Sewell (1952), Stewart (1978), Ede (1987) and Tigges (1988), on nonsense; Huizinga (2010), on game; Watt (2010) and Lukács (2009) on novel; Nikolayeva (2011), on illustration; Pignatari (2011) and Huxley (1948), on poetry; and Agamben (2009), on the contemporaneity. Departing from a historic conceptual recover, our attention is drawn to the perspective of confirmation of the hypothesis about the nonsense literary genre, its connection to the Victorian ages and the reverberations that the referred genre has brought to our contemporaneity, and specially to the novel by Renato Pompeu, leaving as credit the tendency for the fragmentation of the narrative